Comparison of Attachment and Relaxation Training Effects on Anxiety in Third Trimester and Postpartum Depression among Primipara Women - Bahare Rafiee; Marzieh Akbarzade; Nasrin Asadi; Najaf Zare (حیات, 2013)
Background & Aim: Reducing maternal anxiety has a critical role in maternal and fetal mental and physical health. This study aimed to assess the effect of two anxiety reducing techniques including relaxation and maternal-fetal attachment training on anxiety in third trimester and postpartum depression among primipara women.